TRANSFORMASI PELAYANAN ADMINISTRASI KEPENDUDUKAN MELALUI IMPLEMENTASI E-GOVERNMENT - Haerunnisa; Firmansyah (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2025)
The purpose of this study was to determine the implementation of e-government, identify supporting and inhibiting factors of transformation and determine the impact of e-government implementation on the Population and Civil Registration Office of Wajo Regency. This study uses a descriptive qualitative research design with a case study approach at the Population and Civil Registration Office of Wajo Regency. Data collection methods through observation, interviews and documentation. The research findings show that first, the implementation of e-government at the Population and Civil Registration Office of Wajo Regency is a strategic step in order to increase efficiency, transparency, improve data management, reduce operational costs and facilitate access for the community. Second, the supporting and inhibiting factors of digital transformation are seen from the aspects of adequacy of human resources, financial and technological infrastructure, adequacy of the budget to increase the capacity and digital literacy of the community, and the adequacy of facilities and infrastructure of the Population and Civil Registration Office of Wajo Regency. However, in this case, the obstacle is inadequate internet access. Third, the implementation of e-government can increase service efficiency by accelerating document processing, reducing queues, and improving data management processes. However, the implementation of e-government requires adequate internet access, so that areas that have adequate internet access will be limited in the implementation of e-government.